Faktor Determinan Fertilitas Remaja di Provinsi Nusa Tenggara Timur: Determinants of Adolescent Fertility in East Nusa Tenggara Province - Reski Ihsan Humang; Bs. Titi Haerana; Yuniar Dwi Yanti (Poltekkes Kemenkes Palu, 2021)
Introduction: Adolescent fertility caused various negative consequences starting from the occurrence of adolescent fertility include health, social and economic impacts. Purpose: to study the determinants of adolescent fertility in the Province of East Nusa Tenggara. Methods: This study uses secondary survey data in the 2017 IDHS. The sample was adolescents aged 15-19 years who were recorded as selected samples in East Nusa Tenggara Province as many as 401 adolescents. Analysis using multiple logistic regression with predictive factor model. Results: The highest aOR value is marital status 17.25 (95% CI 6.60-45.04). Education only finished elementary school aOR 4.94 (95%CI 1.08-22.45). Never accessed the internet aOR 3.37 (95%CI 0.85-13.37). For every 1 year increase in adolescent age, the odds increased by 3.32 (95% CI 1.71-6.46) or 19 years old had the highest odds. Didn’t work aOR 3.00 (95% CI 0.71-12.66). Living in rural areas aOR 2.55 (95%CI 0.53-12.13). Low knowledge of family planning methods has an AOR of 0.26 (0.05-1.22). Conclusion: The determinants of adolescent fertility in NTT Province are age, education, occupation, marital status, place of residence, internet use and knowledge of family planning methods.